2018
DOI: 10.3389/fbioe.2018.00144
|View full text |Cite
|
Sign up to set email alerts
|

New Thermophilic α/β Class Epoxide Hydrolases Found in Metagenomes From Hot Environments

Abstract: Two novel epoxide hydrolases (EHs), Sibe-EH and CH65-EH, were identified in the metagenomes of samples collected in hot springs in Russia and China, respectively. The two α/β hydrolase superfamily fold enzymes were cloned, over-expressed in Escherichia coli, purified and characterized. The new EHs were active toward a broad range of substrates, and in particular, Sibe-EH was excellent in the desymmetrization of cis-2,3-epoxybutane producing the (2R,3R)-diol product with ee exceeding 99%. Interestingly these en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 90 publications
0
23
0
Order By: Relevance
“…The search of novel HSDH sequences was carried out by using either the Blastp tool (https://blast.ncbi.nlm.nih.gov/) for mining into the NCBI database (https://www.ncbi.nlm.nih.gov/) or the program LAST (http://last.cbrc.jp/) for the analysis of metagenomes of samples collected in hot terrestrial environments . In both cases, only sequences of functionally characterized HSDHs (Table S1 in the Supporting Information) were used as queries during the multiple sequence alignments.…”
Section: Resultsmentioning
confidence: 99%
“…The search of novel HSDH sequences was carried out by using either the Blastp tool (https://blast.ncbi.nlm.nih.gov/) for mining into the NCBI database (https://www.ncbi.nlm.nih.gov/) or the program LAST (http://last.cbrc.jp/) for the analysis of metagenomes of samples collected in hot terrestrial environments . In both cases, only sequences of functionally characterized HSDHs (Table S1 in the Supporting Information) were used as queries during the multiple sequence alignments.…”
Section: Resultsmentioning
confidence: 99%
“…Upon analyzing the structures of both enzymes, some thermal stability (up to 60 • C and little at 70 • C) appears to be due to a significant amount of hydrophobic regions on the protein surface while polar patches were smaller. Ferrandi et al (2018) reported that hydrophobic interactions considered an important feature of a protein to identify its thermostability.…”
Section: Discussionmentioning
confidence: 99%
“…After using PCR to amplify identified DNA, the enzymes were cloned, and assayed for their functionality. Metagenomics has now emerged as a very effective tool to mine for non‐redundant genes, creating panels of enzymes from the same families with low sequence homologies [14,15] …”
Section: Introductionmentioning
confidence: 99%
“…Metagenomics has now emerged as a very effective tool to mine for non‐redundant genes, creating panels of enzymes from the same families with low sequence homologies. [ 14 , 15 ]…”
Section: Introductionmentioning
confidence: 99%